Painel 3 - Cartéis em um contexto global / Cartels in a global context - Andrade, Tito; Bodrug, John; Ryan, Alan; Grinberg, Mauro; Bucci, Maria Paula Dallari; Rosenberg, Bárbara; Marques, Fernando De Oliveira (Revista do IBRAC, 2025)
Chairman Tito Andrade Barbara Rosenberg – Diretora do DPDE/SDE Alan Ryan – Freshfields Bruckhaus Deringer LLP Fernando Marques – Conselheiro do Cade John D. Bodrug – Davies Ward Phillips & Vineberg – Toronto Maria Paula Dallari Bucci – Procuradora-Geral do Cade Mauro Grinberg – Advogado